RELATIONSHIP ANALYSIS BETWEEN CRAB CARAPACE WIDTH AND WEIGHT CAUGHT USING FOLDING TRAPS IN GEBANG MEKAR WATERS - Jhohan; Riyanto, Mochammad; Tapilatu, Maryrose Easter; Bahtiar, Sadida Anindya; Rajagukguk, Bulfrit B.; Sasarari, Rosmina; Soradatu, Syeiqido (Jurnal Penelitian Perikanan Laut (Albacore), 2025)
The blue swimming crab (Portunus pelagicus) is a high economic importance marine species and serves as a primary target for local fisheries employing collapsible traps in Gebang Mekar, Cirebon Regency waters. This study aimed to examine the sex ratio and growth pattern based on variations in carapace width and body weight of crabs captured in the area. Fieldwork was conducted from April to May 2023 in Gebang Mekar Village. Data collection involved measuring the carapace width and body weight of crabs obtained from 30 fishing trips. A total of 2,191 individuals were recorded, comprising 638 males (29.2%) and 1,553 females (70.8%), resulting in a male-to-female ratio of 1:2.4. Carapace width ranged from 6 to 16 cm, while body weight varied between 21 to 338 grams. The analysis of the width-weight relationship yielded a regression coefficient (b) of 2.923, indicating a negative allometric growth pattern, where carapace width increases faster than body weight. The results also demonstrated a positive correlation between carapace width and body weight, suggesting that larger individuals tend to be heavier. Key words: blue swimming crab, carapace width and weight, sex ratio